PENDEKATAN KOMUNIKASI HATI SEBAGAI STRATEGI INTERVENSI PSIKOLOGIS ANAK TERDAMPAK BENCANA - Wahyu Rezeki; Muhammad; Reza Muttaqin (Program Studi Komunikasi dan Penyiaran Islam, 2025)
Children are among the most psychologically vulnerable populations in disaster contexts due to their limited cognitive, emotional, and social capacities. While numerous post-disaster psychological interventions have been developed, many remain technically oriented and insufficiently emphasize emotional relationships and empathic communication as the foundation of recovery. This study aims to conceptually examine heart-based communication (komunikasi hati) as a core psychological intervention strategy for children affected by disasters. Using a library research design with a qualitative descriptive approach, this study analyzes academic books, peer-reviewed journal articles, reports from international organizations, and relevant policy documents on disaster psychology, child interventions, and empathic communication. Data were analyzed through content analysis involving data reduction, thematic organization, and theoretical synthesis. The findings demonstrate that heart-based communication plays a strategic role in fostering children’s sense of safety, trust, and emotional attachment—key elements in post-traumatic recovery. This approach aligns with humanistic theory, attachment theory, and developmental psychology, which emphasize interpersonal relationships as central to psychological change and resilience. Moreover, heart-based communication functions effectively as a low-intensity psychological intervention during the early post-disaster phase, particularly in contexts with limited access to professional mental health services. The novelty of this study lies in positioning heart-based communication not merely as a supportive communication skill, but as a primary and integrative psychological intervention framework for disaster-affected children. These findings contribute to disaster psychology scholarship and offer practical implications for policy development, companion training, and child-centered intervention practices that are empathic, humanistic, and culturally responsive